2019
DOI: 10.18823/asiatefl.2019.16.2.2.468
|View full text |Cite
|
Sign up to set email alerts
|

L2 Learners’ and Professionals’ Perceptions of Cognitive Task Complexity : Towards Developing an Index of Task Difficulty

Abstract: This paper attempts to broaden our understanding on how cognitive task complexity (TC) contributes to L2 learners' and language professionals' perceptions of task difficulty (TD). This study was conducted to allow a deeper investigation of the extent to which manipulating TC can influence perceptions of TD, what TC-factors contribute to perceptions of TD, and whether there is a perceptual match between L2 learners and language professionals. The study employed a mixed-method design in which 68 students and 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Social networking sites in Russian were also used rarely; the same situation was applied to writing emails in Russian. To sum up, both qualitative and quantitative data related to direct spoken communication emphasize the impact of inter-group anxiety and on students' willingness to engage in intercultural communication [20]. The results of this investigation demonstrate that international students from study-abroad programs mainly socialize within their own ethnical group due to high communication anxiety and perceived threats to their self-esteem.…”
Section: Ego-permeabilitymentioning
confidence: 77%
“…Social networking sites in Russian were also used rarely; the same situation was applied to writing emails in Russian. To sum up, both qualitative and quantitative data related to direct spoken communication emphasize the impact of inter-group anxiety and on students' willingness to engage in intercultural communication [20]. The results of this investigation demonstrate that international students from study-abroad programs mainly socialize within their own ethnical group due to high communication anxiety and perceived threats to their self-esteem.…”
Section: Ego-permeabilitymentioning
confidence: 77%
“…It addresses the complexity of tasks across different activities to be trained to use language constructively and appropriately. TBLT can be used as a cognitive load measurement method to obtain empirical evidence that the more complex tasks place a higher cognitive load on the learner, which, in turn, will contribute to structural changes in language performance (Awwad, 2019;Lee, 2019). Kafipour et al (2018) also proposed that TBLT inspire, promote, empower, and challenge participants.…”
Section: The Quality Of the Task-based Materials Design To Improve Ewamentioning
confidence: 99%
“…Due to the complex nature of language proficiency which comprises oral production (Awwad & Alhamad, 2021) and communicative use of a target language in spontaneous and naturalistic contexts, capturing or assessing it accurately using conventional techniques may not be an easy task (Hulstijn, 2015). Language proficiency can be assessed using standard tests (Nakatsuhara, et al, 2019), speech performance (Awwad, et al, 2017), self-reported assessment (Awwad, 2022), learner perception (Awwad, 2019) or teacher awareness (Alhumsi & Awwad, 2020).…”
Section: Introductionmentioning
confidence: 99%